Analisis Keterbukaan Ekonomi terhadap Pertumbuhan Ekonomi di 6 Negara ASEAN - Fatmawati, Anisa; Purnomo, Sodik Dwi; Jati, Damar; Setiawan, Gawik (Nur Science Institute, 2025)
This study aims to analyze the effect of economic openness, inflation, FDI, and government spending on economic growth in six ASEAN countries, including Indonesia, Malaysia, Vietnam, Thailand, Singapore, and the Philippines, from 2009 to 2021. The analysis method used in this study uses panel data analysis using a random effect model (REM) approach. This research shows that economic openness has a significant positive effect, inflation and government spending do not significantly affect economic growth, and FDI has a significant adverse effect on economic growth in six ASEAN countries. This research implies that the government must improve the domestic economy’s performance (producers) through import substitution policies and improved export governance with accommodative policies such as reducing export duties and VAT rates of 0 percent for producers who have just entered export activities. The government needs to improve the availability of market facilities and infrastructure and reduce barriers in exchanges between countries; this is so that there are more market choices for domestic producers to export and market choices for imports at competitive prices and lower costs due to good infrastructure. The limitations of this study are that it only examines the problems of the influence of economic openness, inflation, FDI, and government spending.